2020
DOI: 10.1001/jamanetworkopen.2020.4662
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Maternal Prepregnancy Body Mass Index and Anthropometric Parameters, Blood Pressure, and Retinal Microvasculature in Children Age 4 to 6 Years

Abstract: IMPORTANCE Maternal prepregnancy body mass index (BMI; calculated as weight in kilograms divided by height in meters squared) has previously been associated with offspring cardiometabolic risk factors, such as fat mass, glucose and insulin levels, and blood pressure, but these associations appear to be largely mediated by offspring BMI. To our knowledge, no studies have assessed alterations in the retinal microvasculature in association with maternal prepregnancy BMI.OBJECTIVE To investigate the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 55 publications
0
17
0
1
Order By: Relevance
“…39 The results from this study reinforce previous findings and provide insight into possible mechanisms. Several birth cohort studies (including the one used here) demonstrated that higher maternal pre-pregnancy BMI is positively associated elevated blood pressure at 4-6, 40 9 41 and 15 years of age. 2 Similar associations have been found with exposure to gestational diabetes in utero .…”
Section: Discussionmentioning
confidence: 73%
“…39 The results from this study reinforce previous findings and provide insight into possible mechanisms. Several birth cohort studies (including the one used here) demonstrated that higher maternal pre-pregnancy BMI is positively associated elevated blood pressure at 4-6, 40 9 41 and 15 years of age. 2 Similar associations have been found with exposure to gestational diabetes in utero .…”
Section: Discussionmentioning
confidence: 73%
“…Nine studies report positive associations between MppBMI and offspring childhood anthropometrics ( 30 , 31 , 33 , 35 – 38 , 40 , 41 ). Of these, three studies had critical and two had severe risk of bias, predominantly due to confounding and selection bias ( Table 5 and Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies measured the impact of MppBMI on offspring BP. Five studies found that MppBMI was significantly associated with higher BP in the offspring ( 30 , 33 , 34 , 37 , 38 ) ( Table 5 ). Perng et al.…”
Section: Resultsmentioning
confidence: 99%
“…Inability to vasodilate to meet the demands of the organ are related to the lack of production of NO, prostaglandins and endothelium derived hyperpolarization factors which are effected by inflammation, oxidative stress ( 48 ) and changes in the gene function ( 49 ). These changes have been demonstrated in murine and non-human primates, and more recently these were demonstrated as an abnormality in the retinal microvasculature of children born to women with obesity ( 50 ).…”
Section: Cardiopulmonary Complications Among Offsprings Of Women With...mentioning
confidence: 92%